2019
DOI: 10.3390/su11184854
|View full text |Cite
|
Sign up to set email alerts
|

Path Dependence and Social Network Analysis on Evolutionary Dynamics of Tourism in Coastal Rural Communities

Abstract: The studies on the evolution of tourist destinations are not a new issue, however, most of them have been focused on consolidated destinations, whereas only a minimum has been done on tourism transformation in rural areas. The objective of this work is to diagnose the evolutionary process of tourism in Coastal Rural Communities (CRCs). To do this, we propose a model which combines two research approaches, Path Dependence and Social Network Analysis. The methodological approach is divided into three parts: desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Scholars have conducted extensive research on the motivations of the development of the health tourism industry; these include external driving factors, including world political and economic integration [16][17][18], government support and promotion [19,20], economic and social effects [21,22], network communication technology and information technology revolution [23,24], faster transportation [25] (Rodriguez, 2001), healthy lifestyle of the new generation [26][27][28], population aging and lifestyle changes, the formation of residents' healthy consumption concepts, and tourism consumption demand [29][30][31][32]. Internal driving factors mainly include health tourism resources, such as medical technology and service projects [33], cost and benefit [34], medical equipment [35], and environmental infrastructure [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have conducted extensive research on the motivations of the development of the health tourism industry; these include external driving factors, including world political and economic integration [16][17][18], government support and promotion [19,20], economic and social effects [21,22], network communication technology and information technology revolution [23,24], faster transportation [25] (Rodriguez, 2001), healthy lifestyle of the new generation [26][27][28], population aging and lifestyle changes, the formation of residents' healthy consumption concepts, and tourism consumption demand [29][30][31][32]. Internal driving factors mainly include health tourism resources, such as medical technology and service projects [33], cost and benefit [34], medical equipment [35], and environmental infrastructure [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…However, as tourism became a prominent activity in the region [57], it extended to small communities advertising them as "environmental attractions". This is happening in several regions of Mexico [58,59], but also worldwide as globalized tourism has gained interest in rural communities [60,61]. As PL gained a reputation as a "monkey reserve" and more households engaged in a market economy, CH experienced the opposite trend with tourism agencies reducing their presence, prompting households to diversify their activities, including novel ones, for example charcoal production.…”
Section: Discussionmentioning
confidence: 99%
“…Path dependence is regarded as the engine of regional industrial diversification (Boschma, Ron & Capone, 2016;Aguilar-Becerra et al, 2019;Luhas et al, 2019) where it presents an advanced way to explain the imbalanced development (Walker, 2000;Hidayati, Yamu, & Tan, 2019). Existing studies have demonstrated that the industries in the path have interaction due to upstream and downstream input and output relations, labour sharing, whole service, infrastructure externalities and knowledge spill overs together with the competition of land, capital and skilled labour (Martin & Sunley, 2006).…”
Section: Path Dependence Based On Technological Relatedness--regional Industrial Diversification On the Supply Sidementioning
confidence: 99%